Potential Health and Performance Effects of High-Level and Low-Level Blast: A Scoping Review of Two Decades of Research - Belding, Jennifer N.; Englert, Robyn M.; Fitzmaurice, Shannon; Jackson, Jourdan R.; Koenig, Hannah G.; Hunter, Michael A.; Thomsen, Cynthia J.; da Silva, Uade Olaghere (Frontiers in Neurology, 2021)
Although blast exposure has been recognized as a significant source of morbidity and mortality in military populations, our understanding of the effects of blast exposure, particularly low-level blast (LLB) exposure, on health outcomes remains limited. This scoping review provides a comprehensive, accessible review of the peer-reviewed literature that has been published on blast exposure over the past two decades, with specific emphasis on LLB. We conducted a comprehensive scoping review of the scientific literature published between January 2000 and 2019 pertaining to the effects of blast injury and/or exposure on human and animal health. A three-level review process with specific inclusion and exclusion criteria was used. A full-text review of all articles pertaining to LLB exposure was conducted and relevant study characteristics were extracted. The research team identified 3,215 blast-relevant articles, approximately half of which (55.4%) studied live humans, 16% studied animals, and the remainder were non-subjects research (e.g., literature reviews). Nearly all (99.49%) of the included studies were conducted by experts in medicine or epidemiology; approximately half of these articles were categorized into more than one medical specialty. Among the 51 articles identified as pertaining to LLB specifically, 45.1% were conducted on animals and 39.2% focused on human subjects. Animal studies of LLB predominately used shock tubes to induce various blast exposures in rats, assessed a variety of outcomes, and clearly demonstrated that LLB exposure is associated with brain injury. In contrast, the majority of LLB studies on humans were conducted among military and law enforcement personnel in training environments and had remarkable variability in the exposures and outcomes assessed. While findings suggest that there is the potential for LLB to harm human populations, findings are mixed and more research is needed. Although it is clear that more research is needed on this rapidly growing topic, this review highlights the detrimental effects of LLB on the health of both animals and humans. Future research would benefit from multidisciplinary collaboration, larger sample sizes, and standardization of terminology, exposures, and outcomes.